P217 Chronic mucus hypersecretion may represent a biomarker of airways disease activity rather than simply a phenotype: A longitudinal study of a nationally representative British birth cohort. (12th November 2015) - Allinson, JP; Hardy, R; Donaldson, GC; Shaheen, SO; Kuh, D; Wedzicha, JA
Abstract : Introduction: Chronic mucus hypersecretion (CMH) is associated with COPD development and progression. CMH presence across adult life is dynamic, influenced by factors such as smoking behaviour. CMH is usually considered a binary phenotype and the potential influence of longitudinal CMH pattern on concurrent FEV1 decline has not been explored. We investigated how longitudinal prevalence of CMH relates to concurrent FEV1 decline. Methods: The MRC National Survey of Health and Development consists of a sample of men and women born in one week in March 1946 within England, Scotland and Wales. Smoking behaviour, MRC questionnaire defined CMH, height, weight and pre-bronchodilator spirometry were recorded at three ages: 43, 53 and (60–64) years. We used the number occasions that CMH was positively reported (0–3) as a measure of longitudinal prevalence of CMH. Multilevel models adjusted for sex were used to analyse the relationship between longitudinal prevalence of CMH and concurrent FEV1 decline (between ages 43 and (60–64)), allowing both intercept and slope to vary according to the longitudinal prevalence of CMH score. Height, weight and mean FEV1 at age 43 years were then included in the model. Smoking status (current, ex and never-smoker) and number of cigarettes smoked daily were included as time-varying covariates capable of influencing both intercept and slope. Results: 1960 individuals contributed data to the multilevel model: 46% male; 59% ever-smoker and mean FEV1 at age 43 years = 3.00 L. 13% reported CMH ≥ once between ages 43 and 60–64 years. After full adjustment, longitudinal prevalence of CMH was significantly associated with both a lower FEV1 at age 43 (intercept p < 0.001) and a faster decline (slope p = 0.003) (See Table 1 ). For each additional occasion CMH was reported there was an additional 3.2 ml/yr decline in FEV1 (p = 0.003) i.e. presence of CMH on all three occasions was associated with an additional 9.6 ml/year FEV1 decline compared with those without CMH on any occasion. Conclusion: Longitudinal prevalence of CMH is associated with concurrent FEV1 decline independent of concurrent smoking history. Rather than CMH being solely an airway disease phenotype, the longitudinal course of CMH may represent a biomarker of concurrent disease activity.